(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
3D geometric model of one-seat frame for upholstered furniture was created by the CAD system Autodesk Inventor Pro®. A linear static analysis was carried out with CAE system Autodesk Simulation Mechanicalâ by the method of finite elements (FEM) simulating light-service loading of the frame. The orthotropic material characteristics of pine solid wood (Pinus Sylvestris L.) for the rails and particleboard (PB) for the side plates are considered in the analysis. Corner joints in the framewith staples and PVA glue were considered. FEA was performed with regard to laboratory establishedcoefficients of rotational stiffness of used staple corner joints in the frame – case butt joints and end to face butt joints. As a result, the most loading construction part of the frame with staple corner joints is established – the rear upper rail of the seat where the maximum values for linear displacements,nodal rotationsand stresses are received due to the nature of the applied loading.